Problem-based learning: Creative thinking skills, problem-solving skills, and learning outcome of seventh grade students - Khoiriyah, Anna Jarrotul; Husamah, Husamah (Jurnal Pendidikan Biologi Indonesia, 2018)
Creative thinking skills and problem-solving skills were among the competencies that must be possessed by students in the 21st-century, which need to be developed through the learning process, and are still teacher challenge to date. This study aims to improve creative thinking skills, problem-solving skills, and learning outcomes of seventh-grade students by problem-based learning (PBL). This class action research was conducted at State Junior High School 18 of Malang. The subjects was studentsâ class VIIE. The study was conducted two cycles (repeated seven times). Each cycle referring to Spiral Model by Kemmis, McTaggart, and Nixon. The problem-solving skills data were obtained from student worksheet assessment, the creative thinking skills data were obtained from performance grading rubric and learning outcomes data were obtained from end-of-cycle essay test. The results shows that PBL improves (1) the average of problem solving skills of 27% with the completion rate of 47%,(2) the average of creative thinking skills of 11% with the completion rate of 17.5%, andÂ  (3) the average learning outcomes of 13% with the completion rate of 15%. It can concluded that teachers can implement PBL to improve studentsâ creative thinking skills, problem-solving skills, and learning outcomes.